2008
DOI: 10.1258/td.2007.005274
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of congenital malaria among neonates with suspected sepsis in Calabar, Nigeria

Abstract: We studied the prevalence of congenital malaria among neonates with suspected sepsis and its outcome at the University of Calabar Teaching Hospital, Calabar, Nigeria. All in-born neonates admitted to the newborn unit with clinical features suggestive of sepsis were recruited. They were screened for bacterial sepsis and malaria. The mothers of the neonates that had parasitaemia were further screened for malaria and anaemia. A total of 546 in-born neonates were admitted to the neonatal unit and 202 (37%) present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 10 publications
2
40
0
1
Order By: Relevance
“…Although malaria is endemic in India, neonatal disease is considered rare because of the protection provided by the passive acquisition of maternal antibodies and fetal hemoglobin [2]. The nonspecific signs and symptoms of neonatal malaria are often confused with sepsis, which leads to delay in diagnosis and treatment [2][3][4]. We report a similar incident in which a 26-day-old male neonate was diagnosed as having malaria after a long and unsuccessful battery of tests for splenomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Although malaria is endemic in India, neonatal disease is considered rare because of the protection provided by the passive acquisition of maternal antibodies and fetal hemoglobin [2]. The nonspecific signs and symptoms of neonatal malaria are often confused with sepsis, which leads to delay in diagnosis and treatment [2][3][4]. We report a similar incident in which a 26-day-old male neonate was diagnosed as having malaria after a long and unsuccessful battery of tests for splenomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Being a low endemic region, the median age of presentation tends to be later (8 years) in contrast to the mean age at 26 months reported from Africa [32]. In recent year, workers from endemic areas reported the incidence of neonatal malaria to be 58.5% [4,33]. Studies examining the incidence of parasitemia in infant born in endemic region have shown rates varying from 0-33% [34,35].…”
Section: Burden Of Neonatal Malariamentioning
confidence: 99%
“…So it becomes difficult to assign parasitaemia as a cause of ill health in these newborns. In addition one study suggests that septic neonates and those with suspected sepsis are likely to have parasitaemia [4].…”
Section: Burden Of Neonatal Malariamentioning
confidence: 99%
See 2 more Smart Citations